Penguatan Penguatan Peran Pemuda Dalam Mewujudkan Pemungkiman Sehat dan Kesejahteraan Penduduk di Negara Bagian Terengganu Darul Iman, Malasysia (UIR PRESS, 2024)
Strengthening youth participation in the SDGs needs to be implemented to form self-awareness within youth about their potential in making the SDGs a success. The Sustainable Development Goals (SDGs) are for the purpose of sustainable development. There are seventeen Sustainable Development Goals (SDGs) relating to people, the environment, prosperity, food security, health, peace and partnerships. This service activity focuses on the third goal of the SDGs, namely ensuring a healthy life and promoting prosperity for all people at all ages. The aim of this activity is to increase the role played by youth in Telaga Daing Village, Terengganu Darul Iman State, Malaysia in achieving the third SDGs goal. They need to increase their participation in the SDGs program and increase their self-awareness about their potential. This method of community service uses learning and coaching. From the results of the activities carried out, the service participants gave positive responses, especially regarding the importance of understanding the SDGs and their role in achieving the third goal.